Peran Kepala Madrasah dalam Menemukan Solusi “Jalan Tikus” Pemberantasan Korupsi Melalui Sikap Disiplin di Madrasah Tsanawiyah Swasta Islamiyah At-Taqwa Medan Belawan - Nazza Mahira (Universitas Medan Area, 2023)
located on Cileduk street right next to the KUA Belawan II Office, Medan Belawan District, Medan madya city. Madrasah Tsanawiyah Islamiyah At-Taqwa has its own uniqueness as there is a Socialization Program for planting anti-corruption values taught by teachers to students in learning, especially Civic Education and Islamic Religious Subjects regarding disciplinary attitudes through the direction of the principal as a coach in the program. This study aims first: to describe the role of madrasah heads in finding solutions to the